Mortalin: Protein partners, biological impacts, pathological roles, and therapeutic opportunities - Esfahanian, Niki; Knoblich, Cole D.; Bowman, Gaven A.; Rezvani, Khosrow (Frontiers in Cell and Developmental Biology, 2023)
Mortalin (GRP75, HSPA9A), a heat shock protein (HSP), regulates a wide range of cellular processes, including cell survival, growth, and metabolism. The regulatory functions of mortalin are mediated through a diverse set of protein partners associated with different cellular compartments, which allows mortalin to perform critical functions under physiological conditions, including mitochondrial protein quality control. However, alteration of mortalin’s activities, its abnormal subcellular compartmentalization, and its protein partners turn mortalin into a disease-driving protein in different pathological conditions, including cancers. Here, mortalin’s contributions to tumorigenic pathways are explained. Pathology information based on mortalin’s RNA expression extracted from TCGA (The Cancer Genome Atlas) transcriptomic database indicates that mortalin has an independent prognostic value in common tumors, including lung, breast, and colorectal cancer (CRC). Subsequently, the binding partners of mortalin reported in different cellular models, from yeast to mammalian cells, and its regulation by post-translational modifications are discussed. Finally, we focus on CRC and discuss how mortalin and its tumorigenic downstream protein targets are regulated by a ubiquitin-like protein through the 26S proteasomal degradation machinery. A broader understanding of the function of mortalin and its positive and negative regulation in the formation and progression of human diseases, particularly cancer, is essential for developing new strategies to treat a diverse set of human diseases critically associated with dysregulated mortalin.